Secondary Prevention in Hereditary Breast and/or Ovarian Cancer Syndromes Other Than BRCA. (14th July 2020) - Piombino, Claudia; Cortesi, Laura; Lambertini, Matteo; Punie, Kevin; Grandi, Giovanni; Toss, Angela
Abstract : BRCA1- and BRCA2-associated hereditary breast and ovarian cancer syndromes are among the best-known and most extensively studied hereditary cancer syndromes. Nevertheless, many patients who proved negative at BRCA genetic testing bring pathogenic mutations in other suppressor genes and oncogenes associated with hereditary breast and/or ovarian cancers. These genes include TP53 in Li–Fraumeni syndrome, PTEN in Cowden syndrome, mismatch repair ( MMR ) genes in Lynch syndrome, CDH1 in diffuse gastric cancer syndrome, STK11 in Peutz–Jeghers syndrome, and NF1 in neurofibromatosis type 1 syndrome. To these, several other genes can be added that act jointly with BRCA1 and BRCA2 in the double-strand break repair system, such as PALB2, ATM, CHEK2, NBN, BRIP1, RAD51C, and RAD51D . Management of primary and secondary cancer prevention in these hereditary cancer syndromes is crucial. In particular, secondary prevention by screening aims to discover precancerous lesions or cancers at their initial stages because early detection could allow for effective treatment and a full recovery. The present review aims to summarize the available literature and suggest proper screening strategies for hereditary breast and/or ovarian cancer syndromes other than BRCA.